CLINICAL SYMPTOMS, EFFECTIVE CURE AND HAZARDOUS EFFECTS OF FABRY DISEASE ON HUMAN HEALTH - Ali, Sikander; Naeem, Sania; Faisal, Fatima (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Fabry disease is a lysosomal storage disorder which is caused by the deposition ofglobotriaosylceramide (GL-3) due to the deficiency of a-galactosidase A leading to thechange in metabolism. This is a pan ethnic disorder and more frequently present in malesthan in females. Children may also have the symptoms of this disease. The major symptomsof fabry’s disease are pain in body, anaemia, fever, kidney problems, dermatologicalsymptoms and cardiovascular disease and strokes. The disease can be analysed by the DNAtesting in amniotic cells and chorionic villi and enzyme activity. Atypical variants oravailable genetic therapy may complicate the genetic counselling. The disease specifictreatment has been introduced in which recombinant human galactosidase enzyme is used toinvestigate the fabry’s disease, this treatment is known as enzyme replacement therapy. Renaltransplantation and dialysis have also been introduced. Analgesic drugs, antiarrhythmicagents and nephroprotections are used to relieve pain.